Elsmore, Allen County - Nickell, Paige (Kansas State University, The Chapman Center for Rural Studies, 2017)
This paper shares the history and stories of those in the town of Elsmore, in Elsinore Township, Allen County, Kansas. The town was founded in 1866, and is still occupied today. In this paper, I used newspapers, field work, census data and Kansas directories.
Paige Nickell, “Elsmore, Allen County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/200.
Keywords: Allen County; Danes; Elsinore; Elsmore; Scandinavians; twin towns